Sex-Specific Differences in Lipid and Glucose Metabolism - Varlamov, Oleg; Bethea, Cynthia L.; Roberts, Charles T. (Frontiers in Endocrinology, 2015)
Energy metabolism in humans is tuned to distinct sex-specific functions that potentially reflect the unique requirements in females for gestation and lactation, whereas male metabolism may represent a default state. These differences are the consequence of the action of sex chromosomes and sex-specific hormones, including estrogens and progesterone in females and androgens in males. In humans, sex-specific specialization is associated with distinct body-fat distribution and energy substrate-utilization patterns; i.e., females store more lipids and have higher whole-body insulin sensitivity than males, while males tend to oxidize more lipids than females. These patterns are influenced by the menstrual phase in females, and by nutritional status and exercise intensity in both sexes. This minireview focuses on sex-specific mechanisms in lipid and glucose metabolism and their regulation by sex hormones, with a primary emphasis on studies in humans and the most relevant pre-clinical model of human physiology, non-human primates.